Construction of Pd/BiOCl Catalyst for Highly‐selective Synthesis of Benzoin Ethyl Ether by Chlorine Promoted Coupling Reaction. Issue 11 (15th May 2019) - Yuan, Qinglin; Gong, Wanbing; Ye, Yixing; Liu, Jun; Lin, Yue; Chen, Chun; Zhang, Haimin; Li, Pengfei; Cheng, Weiren; Wei, Xiangjun; Liang, Changhao
Abstract: Exploring novel catalyst supports with unique performance creates more opportunity for transforming organic chemicals in heterogeneous catalysis. In this paper, BiOCl is first presented as an effective support for Pd nanoparticles (NPs) toward application in the coupling reaction of benzaldehyde. The Cl − ion dissociates from BiOCl, which forms nucleophile with Pd nanoparticles; this is key for the one‐step synthesis of benzoin ethyl ether, the conversion and selectivity of which can reach to 100 % and 97.9 % at 100 °C, respectively. DFT calculations reveal that Cl − ions can be stabilized by stronger Bi−Cl bonds through doping of Fe ions in substituting Bi sites in BiOCl. The parallel catalytic evaluation using Pd/Fe‐doped BiOCl catalyst shows the suppression of coupling reaction, conversely, demonstrating the crucial role of nucleophile. This work provides new insights into support tailoring for the synthesis of vital organic chemicals in heterogeneous catalysis by changing chemical reaction pathway. Abstract : Coupling reaction : A novel Pd/BiOCl catalyst is designed to catalyze benzaldehyde for high‐selectively synthesizing benzoin ethyl ether utilizing the nucleophilic action of Cl − ions. DFT calculations and experimental evidences demonstrated the key role of dissociated Cl − ions with Pd NPs by suppressing the dissociation of Cl − ions and changing the reaction pathway.